Implementasi Strategi Pemasaran Untuk Meningkatkan Penjualan di Galeri Ciumbuleuit Hotel - Lilis Putri Anggraeni; Chandra Hendriyani (Jurnal Sekretaris dan Administrasi Bisnis, 2021)
The growing of the tourism sector in various parts of the world makes a big competition occur by promoting the superiority of each country that is not owned by other countries. In this issue there will definitely be ups and downs or increases and decreases that have link with the tourism sector. To stay ahead in the fierce market competition, a good and correct marketing strategies is needed for to not lose the competition and still exist in the tourism. This supports the writing of a practical work report entitled "Implementation of Marketing Strategies to Increase Sales at the Galeri Ciumbuleuit Hotel ", with a tourism background that run hotel and hospitality industry that strongly supports the development of the tourism sector in Indonesia. This research focuses on how to sell the products owned by the Galeri Ciumbuleuit Hotel. The purpose of this study was to determine the process of receiving requests of Galeri Ciumbuleuit Hotel’s products. In addition, to find out the relevant theories are implemented in the sales process carried out by the Galeri Ciumbuleuit Hotel. This field research was carried out in more or less than 3 months. The primary data were obtained from direct observations inside and outside the Galeri Ciumbuleuit Hotel, while the secondary data were obtained from books, documents, and articles relating to the research work report. The results of this study indicate that there is a match between theory and practice in increasing sales at Galeri Ciumbuleuit Hotel. The activities carried out to increase sales have paid attention to marketing strategies in accordance with marketing mix theory. This is done to make it easier to recognize and reach the market so that it can attract a lot of markets as possible. Also to avoid losing competition with competitors.